Effects of heavy ion irradiation on ultra-deep-submicron partially-depleted SOI devices - 武唯康 安霞 谭斐 冯慧 陈叶华 刘静静 张兴 黄如 (Journal of semiconductors, 2015)
The effects of the physical damages induced by heavy ion irradiation on the performance of partiallydepleted SOI devices are experimentally investigated. After heavy ion exposure, different degradation phenomena are observed due to the random strike of heavy ions. A decrease of the saturation current and transconductance,and an enhanced gate-induced drain leakage current are observed, which are mainly attributed to the displacement damages that may be located in the channel, the depletion region of the drain/body junction or the gate-to-drain overlap region. Further, PDSOI devices with and without body contact are compared, which reveals the differences in the threshold voltage shift, the drain-induced barrier lowing effect, the transconductance and the kink effect. The results may provide a guideline for radiation hardened design.